2019
DOI: 10.3350/cmh.2018.0087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bioenergetic and mitochondrial function in liver transplantation

Abstract: Background/Aims We measured changes in mitochondrial function and bioenergetics that occur during ischemia/ reperfusion in fresh liver samples of patients undergoing liver transplantation. These variations correlated with markers of liver function and clinical outcome. Ischemia/reperfusion injury related to liver transplantation affects mitochondrial function and bioenergetics. Experimental studies were conducted to identify the role of bioenergetics and mitochondrial dysfunction. To the best of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“… 8 , 9 It has been demonstrated that mitochondrial respiration, mitochondrial membrane potential and intracellular adenosine triphosphate (ATP) can determine the liver quality prior of transplantation. 10 However, data from direct assessment of mitochondrial function during MP in humans are scarce.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 It has been demonstrated that mitochondrial respiration, mitochondrial membrane potential and intracellular adenosine triphosphate (ATP) can determine the liver quality prior of transplantation. 10 However, data from direct assessment of mitochondrial function during MP in humans are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Both parameters could help predict liver function before liver implantation and liver morbidity and mortality after transplantation [ 187 , 188 ]. A clinical study found that poorly performing mitochondria from human patients were correlated with worse complications after liver transplantation [ 189 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the resection of liver mass, an early, almost immediate, drastic decrease of the hepatic concentration of total adenine nucleotides, not necessarily associated with energy consumption or mitochondrial impairment, has been mainly related with the release of ATP by hepatocytes and non-parenchymal cells, and it appears to constitute a relevant trigger for liver regeneration 8,9,17 . Increased energy consumption or bioenergetic impairment at this stage, manifested as decreases of ATP with parallel increases of ADP and AMP or as mitochondrial dysfunction, however, has been related with extended hepatic resections or other conditions associated with impaired hepatocyte proliferation or impending liver failure 12,15,18,19 . As in prior studies and consistent with the development of post-hepatectomy liver failure, pigs undergoing 90% hepatectomies presented an immediate decrease of ATP associated with concomitant increases of ADP and AMP, resulting in decreases of the energy load and of the ATP/ADP ratio that persisted up to the 24-h time point.…”
Section: Discussionmentioning
confidence: 99%